STRATEGI KOMUNIKASI RIAU VAPER COMMUNITY DALAM KAMPANYE ANTI ROKOK PADA USIA REMAJA DI KOTA PEKANBARU - Ariga Martianov; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Based on data from the Ministry of Health, Riau Province included into the top 5 highest register of the smokers in adolescence with a percentage of 51.3%. As for the city of Pekanbaru, according to data from the Provincial Health Office of Riau percentage of smokers at an early age is increasing every year. The purpose of the study is to determine the communication strategy used by Riau Vaper Community as one community in Pekanbaru city that has a special concern with tobacco cigarettes and tried to give the campaign a way to educate the youth who are vulnerable to the use of tobacco cigarettes.This research using qualitative descriptive methods and data collection techniques are grouped through observation, interviews and documentation. The informant in this research were five people who were taken by purposive sampling technique. Interactive data analysis model the author uses to describe the results of research into techniques for data analysis and data validity checking researchers used a technique extension of participation and triangulation.These results indicate that communication strategies Riau Vaper Community in the campaign is to use the media, especially social media is already widely used youth. The use of social media like Instagram, Facebook, Twitter and Path became the focus of a campaign to be conducted Riau Vaper Community. In addition to social media, Riau Vaper Community also use print media such as newspapers and radio. Riau campaign conducted by the Community Vaper do with the nature of education, choice of words is not complicated and does not use the word term is done so that the audience does not have any errors in response to the message delivered or saturation in listening to the message.keywords: strategy, communication, campaign, descriptive